Analisis Pengaruh Pengaturan Parameter pada CNC Cutting Laser terhadap Kualitas Hasil Pemotongan pada Material Stainless Steel 304 di PT X: - Hadi Nurwahyudin; Mochammad Rajib El Atros; Mualif (Proklamasi 45 University, 2025)
The advancement of manufacturing technology continues to drive optimization in material cutting processes, one of which is the use of CNC Laser Cutting machines. This study aims to analyze the effect of varying cutting parameters on the quality of Stainless Steel 304 cutting results at PT X. The parameters examined include cutting speed, laser power, gas pressure, and focal point. Experiments were conducted by adjusting these parameters and evaluating the results based on dimensional accuracy, surface cleanliness, and cutting quality. The findings indicate that an optimal combination of parameters can enhance cutting quality by reducing defects such as dimensional inaccuracies, rough surfaces, and oxidation on the cutting edges. The study concludes that proper parameter settings are crucial for improving production efficiency and final product quality in the manufacturing industry.